Paleoecology of Organic Deposits of Probable Last Interglacial Age in Northern Ontario - Mott, Robert; DiLabio, Ronald (Géographie physique et Quaternaire, 1990)
ABSTRACTNonglacial deposits in northern Ontario that may date to the last interglacial interval are well known from the Hudson Bay Lowlands where they have been described in sections along several river valleys. Soil horizons, peat beds and other organic sediment sequences comprise the Missinaibi Formation of the Moose River Basin studied for pollen and macrofossils. Results suggest that the climate was as warm or warmer than present, and spruce woodlands prevailed among broad expanses of bog and fen. The Beaver River peat records conditions similar to the present in the Fort Severn area with open spruce woodlands dispersed in peatlands. South of the Lowlands in the Timmins area, a widespread organic-silt horizon termed the Owl Creek beds is stratigraphically equivalent to the Missinaibi Formation. The waning phase of a warm interval is represented, with early climate possibly similar to the present and the later climate much cooler. Correlation of the Missinaibi Formation with substage 5e of the deep-sea oxygen isotope record is corroborated by amino acid results on marine shells from some associated units. Analysis of shells from beneath the Beaver River peat bed indicate that this interval may be considerably younger, possibly substage 5c or, more likely, 5a. The Owl Creek beds may relate to sub-stage 5e, or to one of the younger intervals, 5c or 5a.